The spatio-temporal trends and determinants of liver cancer attributable to specific etiologies: a systematic analysis from the Global Burden of Disease Study 2021 - Jinli Liu; Tingling Xu; Yanan Wang; Fanpu Ji; Lei Zhang (Global Health Research and Policy)
Abstract Background Although liver cancer has varied causes, its evolving epidemiology and causal drivers remain underexplored. This study quantifies the trends and drivers of liver cancer burden attributable to specific causes from 1990 to 2021. Methods Using data from the Global Burden of Disease Study, we extracted prevalence, mortality, and disability-adjusted life years (DALYs) associated with specific causes of liver cancer. We assessed spatio-temporal trends across the sociodemographic index (SDI) and quantified the contributions of epidemiological shifts, population growth, and ageing to DALYs. Results In 2021, liver cancer accounted for 0.74 million cases, 0.48 million deaths, and 12.89 million DALYs globally. Average annual percentage changes (AAPCs) in prevalence, mortality, and DALY rates from 1990 to 2021 were 1.17%, 1.04%, and 0.48%, respectively. HBV, HCV, and alcohol use were major contributors to DALYs, accounting for 1.92 million (36.00%), 1.53 million (28.62%), and 1.27 million (23.88%) of the increase, respectively. High-income North America and Western Europe experienced rapid growth in liver cancer prevalence from 1990 to 2021, while High-income North America and Southern Latin America had rapid growth in mortality. Global DALY increases were mainly driven by population growth (3.91 million, 73.29%) and population ageing (3.03 million, 56.86%). Conclusions The study revealed that hepatitis B, hepatitis C, and alcohol consumption were the primary contributors to the increasing DALYs from liver cancer, with population growth and ageing as key drivers of these changes. These findings underscore the importance of considering the major factors and demographic dynamics in addressing the burden of liver cancer when formulating prevention and intervention strategies.